Kepemilikan Institusional Sebagai Pemoderasi Pengaruh Leverage, Ukuran Perusahaan dan Sensitivitas Kekayaan Eksekutif Terhadap Manajemen Laba - Erlina Angelina; Suci Atiningsih (Journal of Economics and Business, 2020)
This research aims to analyze the effect of leverage, firm size and sensitivity of executive wealth on earnings management with institutional ownership as a moderating variable. With the purposive sampling method obtained as many 70 sample. The type of data used from annual reports. The analytical tool used is multiple linear regression analysis. In this research, the results showed that leverage and sensitivity of executive wealth have a positive effect on earnings management, while firm size has a negative effect on earnings management. Institutional ownership does not moderate firm size, but can moderated leverage and sensitivity of executive wealth on earnings management.